Recurrent Urinary Tract Infections due to Asymptomatic Colonic Diverticulitis - Evangelos Falidas; Georgios Anyfantakis; Stavros Boutzouvis; Michail Kyriakopoulos; Stavros Mathioulakis; Konstantinos Vlachos; Constantinos Villias (Case Reports in Medicine)
Colovesical fistula is a common complication of diverticulitis. Pneumaturia, fecaluria, urinary tract infections, abdominal pain, and dysuria are commonly reported. The authors report a case of colovesical fistula due to asymptomatic diverticulitis, and they emphasize the importance of deeply investigate recurrent urinary tract infection without any bowel symptoms. They also briefly review the literature.